Ligasure hemorrhoidectomy (LH) with „near base“ technique - Tahir, SHenol; Ambardjieva, Martina; Jovanovska, Frosina; Mustafova, Alma; Dervisov, Kristijan; Limani, Nimetula; Dalipi, Berat; Markov, Petar (Springer Science and Business Media LLC, 2021)
Ligasure hemorrhoidectomy (LH) with „near base“ technique Şenol Tahir*, Martina Ambardjieva, Frosina Jovanovska, Alma Mustafova, Kristijan Dervisov, Nimetula Limani, Berat Dalipi, Petar Markov University Clinic for Surgical Diseases, General and Abdominal departemen – St. Naum Ohridski, Skopje, N. Macedonia Background: In this study we evaluate the use of MilliganMorgan hemorrhoidectomy with Ligasure vessel sealing. Methods: Grades 3 and 4 hemorrhoids are operated with Ligasure by coagulation and cutting of the hemorrhoids at positions 5, 7 and 11 hour. Te patients received premedication, analgesia and intravenous 500 mg metronidazole preoperatively. Under anesthesia, placed in a lithotripsy position, the anoscope is placed with a easy retraction, than a 5 mm V shape incision is made with the scalpel at the anocutaneous border. Te nodule was lifted with an instrument and the LigaSure was placed on the base of the nodule (leaving 2 mm enough mucosa above the sphincter), coagulated and incised. Te control check, 24 hours later and sent home with oral analgesic and metronidazole therapy. Follow-up 7, 14 and 28th day Results: 52 patients undergoing LH surgery, with an average age of 42.5 years. 59 % are women and 56 % are grades III. Average operative intervention 17.0+4.1 minutes, hospital stay 1.2 days, Postoperative pain (VAS1-6) 3. Urinary retention 0.4 %. Minor bleeding 5.6 %. Pruritus in 5.6 %, gas incontinence 7.6 %. No stenosis or incontinence. Conclusions: LH is an efective and safe surgical method and it should be used as a routine.
Keywords: Hemorrhoidectomy; Vessel sealing